Low MiR-187 Expression Promotes Resistance to Chemoradiation Therapy In Vitro and Correlates with Treatment Failure in Patients with Esophageal Adenocarcinoma - Niamh Lynam-Lennon; Becky A S Bibby; Ann Marie Mongan; Laure Marignol; Christian N Paxton; Katherine Geiersbach; Mary P Bronner; Jacintha O'Sullivan; John V Reynolds; Stephen G Maher (BMC, 2016)
Abstract Esophageal adenocarcinoma (EAC) has a poor prognosis and is increasing in incidence in many Western populations. Neoadjuvant chemoradiation therapy (CRT) followed by surgery is increasingly the standard of care for locally advanced EAC; however, resistance to treatment is a significant clinical problem. The identification of both novel biomarkers predicting response to treatment and novel therapeutic targets to enhance the efficacy of CRT is key to improving survival rates in EAC. In this study, we performed global microRNA (miRNA) profiling of pretreatment EAC biopsies and identified 67 miRNAs significantly altered in patients who are resistant to CRT. One of these miRNAs, miR-187, was significantly decreased in pretreatment EAC tumors from patients having a poor response to neoadjuvant CRT, highlighting downregulation of miR-187 as a potential mediator of treatment resistance in EAC. In vitro, miR-187 was demonstrated to play a functional role in modulating sensitivity to X-ray radiation and cisplatin in EAC and its dysregulation was demonstrated to be due to chromosomal alterations. In vitro, miR-187 altered expression of a diverse array of pathways, including the immune regulator complement component 3 (C3), serum levels of which we have previously demonstrated to predict patient response to CRT. In vivo, expression of C3 was significantly increased in tumors from patients having a poor response to CRT. This study highlights for the first time a role for miR-187 as a novel biomarker of response to CRT and a potential therapeutic target for enhancing the efficacy of CRT in EAC.